Putting pain in its proper place. (11th June 2018) - Reuter, Kevin; Sienhold, Michael; Sytsma, Justin
Abstract: In a series of articles in this journal, Michael Tye (2002) andPaul Noordhof (2001, 2002 ) have sparred over the correct explanation of the putative invalidity of the following argument: the pain is in my fingertip; the fingertip is in my mouth; therefore, the pain is in my mouth. Whereas Tye explains the failure of the argument by stating that "pain "creates an intensional context, Noordhof maintains that the "in" in 'the pain is in my fingertip' is not spatial, but has state-attributing character. In this paper, we offer a third account, explaining the failure of the argument through state-attributing pragmatic implicatures . Empirical evidence is provided in support of this account.